Using a Values‐Based Taxonomy in Counselor Education. Issue 2 (13th October 2013) - Dollarhide, Colette T.
<x xml:space="preserve">Abstract</x> Values such as respect for the client's privacy and respect for diversity are integral to training new counselors. This requires learning in the affective domain, defined as the internalization of values (Krathwohl, Bloom, & Masia, 1964). The affective taxonomy of Krathwohl et al. (1964) is presented as a means of teaching values and measuring the internalization of values. An example from a multicultural counseling course is offered as a template for implications in counselor education.